Cancer: A Mortal Diease And Improvement In The Technologies of Treatments - Pandey, Shivanand (International Journal of Pharmaceutical & Biological Archive, 2010)
Cancer is second only to heart disease as the leading cause of death in the world. Although surgical resection is considered to be the only approach that offers a possibility of cure to patients with cancer, the prognosis of the disease has not been improved markedly by any surgical procedures in the past 20 years. Although preoperative chemo radiation has various advantages in the treatment of cancer, it does not contribute to its down staging and eventual cure. Our review underscores the complexity of pathogenic mechanisms mediated by chronic inflammation, and identification of enzymes as a target to cure the cancer. The name of cancer is derived from the type of tissue in which it develops. Most human cancers are carcinomas, malignant tumors that arise from epithelial cells. Melanomas are cancerous growths of melanocytes, skin epithelial cells that produce the pigment melanin. Sarcoma a cancer arising from muscle cells or connective tissues. Leukemia is a cancer of blood forming organs characterized by rapid growth of abnormal leukocytes.